2019
DOI: 10.1302/2046-3758.81.bjr-2018-0060.r1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical forces on osteogenesis and osteoclastogenesis in human periodontal ligament fibroblasts

Abstract: ObjectivesMany in vitro studies have investigated the mechanism by which mechanical signals are transduced into biological signals that regulate bone homeostasis via periodontal ligament fibroblasts during orthodontic treatment, but the results have not been systematically reviewed. This review aims to do this, considering the parameters of various in vitro mechanical loading approaches and their effects on osteogenic and osteoclastogenic properties of periodontal ligament fibroblasts.MethodsSpecific keywords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 55 publications
(174 reference statements)
9
55
0
Order By: Relevance
“… 4 , 5 They are involved in a variety of biological processes through their regulatory function in mechanisms of post-transcriptional gene expression ( Table I ). 6 - 10 Cell and animal studies have demonstrated that miRNAs are altered during muscle cell proliferation, differentiation, apoptosis, and regeneration. 2 , 3 , 6 In recent years, miRNAs have emerged as regulators of skeletal muscle function and aberrant expression of miRNAs is thought to be associated with the progression of muscle atrophy in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 They are involved in a variety of biological processes through their regulatory function in mechanisms of post-transcriptional gene expression ( Table I ). 6 - 10 Cell and animal studies have demonstrated that miRNAs are altered during muscle cell proliferation, differentiation, apoptosis, and regeneration. 2 , 3 , 6 In recent years, miRNAs have emerged as regulators of skeletal muscle function and aberrant expression of miRNAs is thought to be associated with the progression of muscle atrophy in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically activated PdL cells therefore release crucial factors that modulate the initiated local inflammation together with differentiation programs of diverse cells regulating alveolar bone remodeling processes 8,9 . Among PdL cells, PdL fibroblasts show many osteoblast-like properties, as they express osteogenic markers like alkaline phosphatase and form mineralized nodules in vitro 1012 . Furthermore, they also have important roles in osteoclastogenesis 12,13 and are therefore a suitable cell culture system to study mechanical-induced changes in vitro 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Among PdL cells, PdL fibroblasts show many osteoblast-like properties, as they express osteogenic markers like alkaline phosphatase and form mineralized nodules in vitro 1012 . Furthermore, they also have important roles in osteoclastogenesis 12,13 and are therefore a suitable cell culture system to study mechanical-induced changes in vitro 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well accepted that the cementoblasts lining the root surface play an important role in preventing root resorption during orthodontic tooth movement, the causes and predisposing factors for orthodontically induced root resorption are not fully understood [11]. Several studies have confirmed the destructive effect of leptin on periodontal fibroblasts [6,[12][13][14]. Here, it has been shown that higher leptin levels are associated with an upregulation of somatostatin receptor 2, indicating a potential mechanism how adipokines could contribute to periodontal destruction through their proinflammatory characteristics [14].…”
Section: Introductionmentioning
confidence: 99%